Meningkatkan Sikap Rasa Ingin Tahu Melalui Penerapan Model Project Based Learning - Panut Setiono; Sri Dadi; Nani Yuliantini (Jurnal Bidang Pendidikan Dasar, 2021)
Curiosity is a character that must be mastered by students to be able to learn independently. The purpose of this study was to determine the increase in the attitude of curiosity in grade 7A students. The research method used in this research is the Classroom Action Research model of Kemmis, Taggart & Nixon with the stages of planning, implementing, observing, and reflecting activities. The data collection instruments used in this study were the observation sheet of learning implementation and a curiosity attitude questionnaire. From the results of observations of the implementation of learning, there was an increase in the implementation of the PjBL learning model from cycle I and cycle II with a percentage score of 70.0 and 84.17. While the results of the questionnaire attitude of curiosity showed an increase in very high criteria with a score of 9.38% in the first cycle, an increase of 15.63% in the second cycle. So that it can be concluded that the PjBL model can increase the curiosity of students.